Strain dependent magnetocaloric effect in La0.67Sr0.33MnO3 thin-films - Kumar, V. Suresh (2013)
The strain dependent magnetocaloric properties of La0.67Sr0.33MnO3 thin films deposited on three different substrates (001) LaAlO3 (LAO), (001) SrTiO3 (STO), and (001) La0.3Sr0.7Al0.65Ta0.35O9 (LSAT) have been investigated under low magnetic fields and around magnetic phase transition temperatures. Compared to bulk samples, we observe a remarkable decrease in the ferromagnetic transition temperature that is close to room temperature, closely matched isothermal magnetic entropy change and relative cooling power values in tensile strained La0.67Sr0.33MnO3 films. The epitaxial strain plays a significant role in tuning the peak position of isothermal magnetic entropy change towards room temperature with improved cooling capacity.